Discussion on Radio: Dilema Keuangan Generasi Sandwich - Alpiansah, Restu; Ramdani, Rizal; Komala, Rina; Dethan, Stevany Hanalyna (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
The Sandwich Generation has financial difficulties. They are unable to handle additional tasks due to a shortage of resources and the presence of multiple personal obstacles. Residing with their family poses more financial issues due to the additional intricacy of financial planning. This article offers an extensive examination and discourse on the financial difficulties encountered by the sandwich generation, as well as possible solutions. To tackle the financial crisis, the sandwich generation must be provided with extensive financial literacy instruction. This service is provided through a live discourse program aired on Fresh Radio station 95.9 FM. The radio is widely embraced by the younger demographic in Lombok Island.  The primary impact of this community project is to cultivate awareness and comprehension among the younger generation regarding effective money management strategies. It is important to aggressively educate the younger generation, especially the sandwich generation, on financial literacy to develop their understanding of financial matters and improve their skills in managing their finances.